Threats to Australia's oceans and coasts: A systematic review. (1st January 2023) - Laubenstein, Taryn; Smith, Timothy F.; Hobday, Alistair J.; Pecl, Gretta T.; Evans, Karen; Fulton, Elizabeth A.; O'Donnell, Tayanah
Abstract: Oceans and coasts provide important ecosystem, livelihood, and cultural values to humans and the planet but face current and future compounding threats from anthropogenic activities associated with expanding populations and their use of and reliance on these environments. To respond to and mitigate these threats, there is a need to first systematically understand and categorise them. This paper reviewed 226 articles from the period 2010–2020 on threats to Australia's oceans and coasts, resulting in the identification of a total of 307 threats. Threats were grouped into three broad categories — threats from use and extraction; environmental and human-induced threats; and policy and socio-political threats —then ranked by frequency. The most common 'threats from use and extraction' were recreational activities, non-point source pollution, and urban development; the most common 'environmental and human-induced threat' was increased temperatures; and the most common 'policy and socio-political threat' was policy gaps and failures (e.g., a lack of coastal climate adaptation policies). The identification of threats across all three categories increased over time; however, the identification of 'threats from use and extraction' increased most rapidly over the last four years (2017–2020). Threats were most often described for their impacts on environmental values (68%), followed by economic (14%), socio-cultural (12%), and Indigenous (6%) values. Only 45 of the 226 papers (20%) discussed multiple threats. The threats facing Australia's oceans and coasts are rising, cumulative, and multi-faceted, and the inherent tensions between varied uses, along with intensification of uses that derive short-term anthropogenic benefit, will continue to degrade the ecological sustainability of ocean and coastal systems if actions are not taken. Graphical abstract: Image 1 Highlights: Threats to Australia's oceans and coasts described in the academic literature from 2010 to 2020 were systematically reviewed. 307 threats were identified across three categories, with most threats in the group "environmental and human-induced threats". Threats were described as impacting environmental (68%), economic (14%), socio-cultural (12%), and Indigenous (6%) values. Only 45 of the 226 papers (20%) discussed multiple threats. Findings highlight the cumulative and multi-faceted threats facing Australian oceans and coasts that must be addressed.